Prophylactic intravitreal injection of aflibercept for preventing postvitrectomy hemorrhage in proliferative diabetic retinopathy: A randomized controlled trial - Jinfeng Qu; Xiuju Chen; Qinghuai Liu; Fang Wang; Mingxin Li; Qiong Zhou; Jin Yao; Xiaoxin Li; Xiaoxin Li (Frontiers Media S.A., 2023)
IntroductionThe aim of this study was to assess the effects of preoperative intravitreal aflibercept (IVA) injection on the incidence of postoperative vitreous hemorrhage (VH) after vitrectomy for proliferative diabetic retinopathy (PDR).MethodsThis study involved a prospective, randomized clinical trial. One hundred twenty-eight eyes of 128 patients of PDR who underwent pars plana vitrectomy (PPV) were enrolled. Sixty-four eyes were assigned randomly to either the IVA group (IVA injection 1 to 5 days before PPV) or the control group (no IVA injection). The primary outcome was the incidence of VH at 1 month after PPV. Secondary outcome measures were best-corrected visual acuity (BCVA) changes from baseline to at 1 week, 1 month, 2 months, and 3 months after surgery.ResultsThe VH incidences in the IVA group and the control group were 14.8 and 39.3% at week 1, 8.6 and 31.7% at month 1, 11.7 and 30.5% at month 2, and 8.6 and 30.5% at month 3, respectively. Intergroup differences showed a significantly decreased VH rate in the IVA group compared with that in the control group at week 1, month 1, and month 3 (p = 0.021, 0.006, and 0.047, respectively). Compared to the baseline, neither the mean BCVA nor the BCVA change in the Logarithm of the Minimum Angle of Resolution (logMAR) scale did differ significantly between the two groups at each visit point. There are a greater number of eyes with BCVA improvement of more than 2 logMAR in the IVA group than in the control group at week 1 (8 vs. 2, p = 0.048).ConclusionsThis study found that the adjunctive use of preoperative IVA reduces early and late postoperative VH in vitrectomy for PDR.